The Toll-Like Receptor 2 Ligand Pam2CSK4 Activates Platelet Nuclear Factor-κB and Bruton’s Tyrosine Kinase Signaling to Promote Platelet-Endothelial Cell Interactions - Parra-Izquierdo, Iván; Lakshmanan, Hari Hara Sudhan; Melrose, Alexander R.; Pang, Jiaqing; Zheng, Tony J.; Jordan, Kelley R.; Reitsma, Stéphanie E.; McCarty, Owen J. T.; Aslan, Joseph E. (Frontiers in Immunology, 2021)
Circulating platelets establish a variety of immunological programs and orchestrate inflammatory responses at the endothelium. Platelets express the innate immunity family of Toll-like receptors (TLRs). While TLR2/TLR1 ligands are known to activate platelets, the effects of TLR2/TLR6 ligands on platelet function remain unclear. Here, we aim to determine whether the TLR2/TLR6 agonists Pam2CSK4 and FSL-1 activate human platelets. In addition, human umbilical vein endothelial cells (HUVECs) and platelets were co-cultured to analyze the role of platelet TLR2/TLR6 on inflammation and adhesion to endothelial cells. Pam2CSK4, but not FSL-1, induced platelet granule secretion and integrin αIIbβ3 activation in a concentration-dependent manner. Moreover, Pam2CSK4 promoted platelet aggregation and increased platelet adhesion to collagen-coated surfaces. Mechanistic studies with blocking antibodies and pharmacologic inhibitors demonstrated that the TLR2/Nuclear factor-κB axis, Bruton’s-tyrosine kinase, and a secondary ADP feedback loop are involved in Pam2CSK4-induced platelet functional responses. Interestingly, Pam2CSK4 showed cooperation with immunoreceptor tyrosine-based activation motif (ITAM)-mediated signaling to enhance platelet activation. Finally the presence of platelets increased inflammatory responses in HUVECs treated with Pam2CSK4, and platelets challenged with Pam2CSK4 showed increased adhesion to HUVECs under static and physiologically relevant flow conditions. Herein, we define a functional role for platelet TLR2-mediated signaling, which may represent a druggable target to dampen excessive platelet activation in thrombo-inflammatory diseases.